2013
DOI: 10.1002/adsc.201200832
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Palladium‐Catalyzed CO Hydrogenolysis of Benzylic Alcohols and Aromatic Ketones with Polymethylhydrosiloxane

Abstract: Scheme 7. Possible explanation for the palladium-catalyzed reductive deoxygenation of aromatic alcohols and ketones.Scheme 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…For example, benzyl alcohol was reduced in 54% yield after 3 h using Pd/C catalyst in compressed CO 2 /water and 1 MPa H 2 [4]. Independently, Huang et al [5] obtained toluene in 98% yield through the reduction of benzyl alcohol using iridium catalyst with hydrazine at 160°C after 3 h. Wang et al [6] reported benzyl alcohol hydrogenolysis in 99% yield using PdCl 2 and PMHS after 12 h at 40°C.…”
Section: Catalytic Performances Of Pd Nps/rgomentioning
confidence: 95%
See 2 more Smart Citations
“…For example, benzyl alcohol was reduced in 54% yield after 3 h using Pd/C catalyst in compressed CO 2 /water and 1 MPa H 2 [4]. Independently, Huang et al [5] obtained toluene in 98% yield through the reduction of benzyl alcohol using iridium catalyst with hydrazine at 160°C after 3 h. Wang et al [6] reported benzyl alcohol hydrogenolysis in 99% yield using PdCl 2 and PMHS after 12 h at 40°C.…”
Section: Catalytic Performances Of Pd Nps/rgomentioning
confidence: 95%
“…It should be noted that this procedure allowed the reduction of benzyl alcohol derivatives in relatively short reaction times and mild conditions as compared to the methods described in the literature [4][5][6]. For example, benzyl alcohol was reduced in 54% yield after 3 h using Pd/C catalyst in compressed CO 2 /water and 1 MPa H 2 [4].…”
Section: Catalytic Performances Of Pd Nps/rgomentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the oxidative addition of Pd(0) to benzylic alcohols to form the palladium hydride intermediate I , which reacts with HCl that is generated in the reaction mixture to afford the corresponding halogenated palladium intermediate II . Then, in the presence of a hydrogen source, the intermediate II further transforms into the hydrocarbons …”
Section: C‐methylationmentioning
confidence: 99%
“…[11] To date, several transition-metal-based catalytic protocols employing PMHS as the reducing agent have been developed for the reduction of amides to amines, [12] as well as for the conversion of ketones, aldehydes, and esters either into alcohols [13] or to saturated alkanes. [14] Although homogeneous systems for the deoxygenation of aromatic alcohols, aldehydes, and ketones with PMHS have been developed, [15,16] there exists no heterogeneous catalytic system for the deoxygenation of aromatic ketones and aldehydes under hydrosilylation conditions. Heterogeneous protocols are generally associated with several practical advantages, such as improved catalyst stability, simpler separation and purification procedures, possibility of catalyst recycling, and lower levels of metal impurities in the final product.…”
mentioning
confidence: 99%